'I've Been There, Done That…': A Study of Youth Gang Desistance. (August 2015) - Gormally, Sinéad
This article, based on research conducted in Glasgow, Scotland, analyses the complex process of desistance from youth gangs. The discussion is multifaceted focusing on the agency of the young people themselves as well as on how relationships within their local community can have a role in replacing their previous identification as gang members. It explores what is meant by a youth gang, why some young people stop identifying with the youth gang and argues that the local community and broader society have a role in providing social recognition and identity-enhancement opportunities for these young people.